The food and weight combat. A problematic fight for the elite combat sports athlete - Pettersson, S.; Pipping Ekström, M.; Berg, C. M. (Appetite, 2012)
Weight reduction in athletes is motivated by optimisation of performance, aesthetic reasons or to achieve a pre-designated weight. Previous research has shown that dietary restraint and short term weight regulation frequently takes place among combat sports athletes such as wrestlers and judokas. The aim of this study was to explore negative experiences related to dietary strategies and weight-making practises used by elite combat sports athletes. Using semi-structured interviews, 14 Swedish national team athletes in wrestling, judo and taekwondo were asked about their dietary intake and their engagement in both long- and short-term weight regulation practises. Content analysis of the transcribed interviews, display a constant struggle regarding nutritional standpoints. Sport demands such as achieving an optimal weight and nutritional intake were considered as central in order for excellent performance. Adhering to these demands was found to be problematic however, primarily because of; (1) negative physiological responses and (2) opposing ideals of a non-sport related nature, such as the importance of the athletes to be healthy and social in their everyday lives.